Effects of survivin and survivin inhibition in canine models of lymphoma and osteosarcoma - Shoeneman, Jenette K., author; Thamm, Douglas, advisor; Gustafson, Daniel, committee member; Duval, Dawn, committee member; Biller, Barbara, committee member; Ehrhart, EJ, committee member (Colorado State University. Libraries, 2014)
Canine lymphoma (LSA) and osteosarcoma (OS) have high mortality rates and remain in need of more effective therapeutic approaches. Survivin, an IAP (inhibitor of apoptosis) family member protein that inhibits apoptosis and drives cell proliferation, is commonly elevated in human and canine cancer. Survivin expression is a negative prognostic factor in both dogs and humans with LSA and OS, and canine LSA and OS cell lines express high levels of survivin. Due to the strong similarities between canine and human LSA and OS, canine LSA and OS are excellent models for the human disease. In the following research, we illustrate the potential of the canine LSA and OS models as a translational tool for evaluating survivin-directed therapies, owing to the striking similarities in gross and microscopic appearance, biologic behavior, gene expression and signaling pathway alterations compared to the respective human forms of these diseases. In this research we sought to determine the effects of survivin inhibition in canine OS and LSA cell lines in vitro, and in vivo in canine OS, and to evaluate a correlation between survivin expression and outcome in canine OS patients. We hypothesized, as observed in human OS and LSA, that survivin inhibition would decrease cell proliferation and increase apoptosis and chemosensitivity in canine OS and LSA cell lines. We further hypothesized that we would observe inhibition of survivin and reduced tumor growth in murine models of canine OS treated with EZN-3042, an inhibitor of survivin. We additionally hypothesized, as observed in human OS, that increased survivin expression would correlate with a poor prognosis in canine OS patients. Survivin attenuation in canine OS cells via siRNA was confirmed by RT-PCR and western blot analysis. Cell number and viablility was assessed via manual cell counting with trypan blue. Cellular apoptosis was confirmed via caspase-3/7 and TUNEL assays. Cell cycle analysis was performed with propidium iodide staining followed by flow cytometry. Chemosensitivity to doxorubicin (DOX) was also assessed with caspase-3/7 assay. We determined that survivin inhibition via siRNA in canine OS cells inhibited cell cycle progression, and increased apoptosis, mitotic arrest and chemosensitivity. Next we inhibited survivin using EZN-3042, a locked nucleic acid oligonucleotide targeting survivin, in two canine LSA and two canine OS cell lines. Survivin inhibition was confirmed by qRT-PCR and Immunofluorescence. Percent dead and total cell number were assessed by manual cell counting with trypan blue. Growth inhibition was confirmed with a bioreductive fluorometric assay. A caspase-3/7 assay was used to determine levels of apoptosis and chemosensitivity. Survivin inhibition in vitro using EZN-3042 resulted in decreased total and viable cell numbers and increased apoptosis and chemosensitivity to DOX. In vivo, nude mice with subcutaneous and orthotopic OS xenografts were given 100 mg/kg EZN3042 intraperitoneally. Survivin inhibition was confirmed with immunohistochemistry and qRT-PCR analysis. EZN-3042 treatment in vivo in subcutaneous and orthotopic canine OS xenografts decreased tumor survivin expression. Mice treated with EZN-3042 in combination with DOX had significantly decreased tumor growth when compared to single agent treatment and control groups. Lastly, we evaluated survivin expression in archived paraffin embedded canine OS tissue samples. Survivin expression was studied via immunohistochemistry in 67 canine OS cases. Elevated survivin protein immunoreactivity in primary canine OS tissue samples correlated with increased histologic grade and mitotic index and a decreased disease free interval (DFI). These findings strongly suggest that survivin-directed therapies may be highly effective in treatment of both canine and human LSA and OS, and spontaneous canine cancer may be a valuable model for the evaluation of survivin-targeted treatment.
Keywords: EZN-3042; translational; survivin; lymphoma; osteosarcoma; cancer